Effects of Channel Redredging on Wildlife and Wildlife Habitat of Buena Vista Marsh - Vandre, Wayne G. (University of Wisconsin-Stevens Point, 1975)
A two-year study was conducted on drainage ditches in a 13 square mile study area of the Buena Vista Marsh, Portage County, Wisconsin, to determine what effect channel maintenance by dredging has on the wildlife of the area and on the wildlife habitat. A 3-mile section of Ditch-3, dredged in 1967-68, was compared to an adjacent 2-mile control section which was last dredged in 1921. The dredging widened the channel an average of 7.9 feet, eliminated meanders and pools, and created a flat stream bottom of homogeneous structure. Silt accumulation was absent in the control section but was present in depths from 1 to J feet in the dredged section after the spring run-off subsided. Sheet-water covered a maximum of 4826 acres of the study area during the spring of 1973 and 832 acres in 1974, a decrease of 83 percent due to reduced amounts of precipitation. This was accompanied by a waterfowl breeding population of 5.4 ducks per square mile in 1973 and 2.6 per square mile in 1974, a reduction of 52 percent. The nearest edge of the sheet-water was located an average of 87 feet from the dredged section of the ditch and an average of 274 feet on the control section. The dredging thus reduced the sheet-water on the study area by 136 acres. Ground water levels were 5.16 inches lower on the area adjacent to the dredged section when compared to a comparable area on the control section. Fifty-one percent of the dabbling ducks were found on sheet-water areas and 14 and 35 percent on ditches and stock ponds, respectively, in 1973. Waterfowl numbers decreased from 1455 in 1973 to 316 in 1974, while usage in 1974 was 52, 11, and 37 percent for sheet-water, ditches, and stock ponds, respectively. Diving ducks did not decrease in numbers and were found almost exclusively on the deeper stock ponds. Nest predation was highest on the ditch banks and the chief predator was the striped skunk. The principal nesting species was the blue-winged teal with an overall nesting success of 38 percent and 20 percent on the ditch banks. Teal nests were located within 80 feet of water during incubation, but those nests adjacent to sheet-water did. not retain this proximity by hatching time because the sheet-water had disappeared. Ditches provided the only available brood habitat. Waterfowl production was 7.48 broods per mile of ditch in 1973, and 0.62 per mile in 1974. Twice as many broods utilized the control section of the ditch as compared to the dredged section in 1973. Waterfowl hunting opportunities were limited to the opening hours of the season. The majority of the blue-winged teal migrated prior to season's opening and those remaining were quite accessible. Bunting success in 1973 was 0.63 birds per hunter. Accessibility to all ditches and lack of any refuge decreases the amount of waterfowl hunting opportunities. Vegetation was absent on the ditch bank subsequent to the dredging operation and on the dredged section now consists of grasses, a few forbs and scattered dogwood and aspen plants. The control section has a grass and forb ground cover with abundant shrub growth consisting of pin cherry, aspen, and dogwood. Trees of these species constitute 763 stems per acre and range from 0.8 to 6.2 inches d.b.h.. Non-game bird species were found to be fewer on the dredged section of Ditch-3 than on the control section. Total species counted on the dredged section in 1973 was 8, while there were 18 species on the control section. Comparable figures for 1974 were 9 and 15 for the dredged and control sections, respectively. The number of species was found to be a better indicator of habitat quality than total number of birds present. Trapping of small mammals on the dredged section of Ditch-3 showed the meadow vole to be the most prevalent species during both years. The white-footed mouse was the most common mammal caught on the control section. The control section also had the greatest diversity of species on the ditch bank. The striped skunk was the most common of the larger mammals caught on the ditch banks. Others caught were raccoon, badger, and Franklin ground squirrel. White-tailed deer used the ditches as watering sites and were present on the marsh with a density of 32 +/- 2 per square mile.